2015
DOI: 10.2174/1381612821666150506154434
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Non-Antimicrobial Drugs and Clinical Molecules to Treat Bacterial Infections

Abstract: There is a pressing need to develop novel antimicrobials to circumvent the scourge of antimicrobial resistance. The objective of this study is to identify non-antibiotic drugs with potent antimicrobial activity, within an applicable clinical range. A library, containing 727 FDA approved drugs and small molecules, was screened against ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter cloacae). Drugs that showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 13 publications
3
68
3
Order By: Relevance
“…Given the need for novel antimicrobials and many appeals of drug repurposing, we performed a whole-cell screening assay to identify Food and Drug Administration (FDA) approved non-antimicrobial drugs with antimicrobial activity toward the ESKAPE pathogens [10]. The screening of a library containing 727 FDA approved drugs and small molecules has produced promising results and has proven to be successful for the identification of novel antimicrobial drugs and new leads for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Given the need for novel antimicrobials and many appeals of drug repurposing, we performed a whole-cell screening assay to identify Food and Drug Administration (FDA) approved non-antimicrobial drugs with antimicrobial activity toward the ESKAPE pathogens [10]. The screening of a library containing 727 FDA approved drugs and small molecules has produced promising results and has proven to be successful for the identification of novel antimicrobial drugs and new leads for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we assembled and screened one-half of all commercially available drugs (ca. 2200 drugs) and small molecules used in human clinical trials [2,12] and identified three drugs (auranofin, ebselen and 5-fluoro-2'-deoxyuridine) [2,13,14] that exhibited potent antibacterial activity against important clinical pathogens. One of these drugs, auranofin, was found to inhibit the growth of clinical isolates of MRSA at submicrogram/mL concentrations in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed 2 nonantibiotic drugs to have bactericidal activity in an animal model, a result that suggests potential clinical usefulness. 18 Another innovative technique is the adjunctive use of hyperbaric oxygen, which has been reported to be useful in a case of Pseudomonas keratitis. 19 A higher percentage of keratitis episodes in the drugsensitive group resolved with medical therapy alone compared with the MDR-PA group (55.22% vs. 34.78%), although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%